PAYUNG HUKUM TERHADAP PROFESI DOKTER DALAM MENGHADAPI PERSELISIHAN MEDIS - Anita Rahayu; Rokhmat; Vera dumonda silitonga; M. Nasser; Tri Agus suswantoro (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Administrative policies or legal provisions in hospital health services certainly regulate procedures for providing adequate and appropriate health services in accordance with hospital service standards, operational standards and professional standards. The problems raised in this research are 1). What is the legal protection for the medical profession in dealing with medical disputes, and 2). What are the hospital's responsibilities towards doctors in dealing with medical disputes? The type of research that will be used in this research is normative juridical which refers to legal norms contained in statutory regulations. The approach used is the Legal Approach and Conceptual Approach and the data obtained is secondary data consisting of primary legal material, secondary legal material and tertiary legal material. To analyze the data using qualitative analysis. The results of this research are legal protection for the medical profession in handling medical disputes with patients, namely doctors who have carried out their duties in accordance with professional standards, service standards and standard operational procedures are entitled to legal protection. and the hospital as the person responsible will take a series of steps. First, form an instrument whose task is to assist directors, for example the legal commission, to handle legal aspects related to matters relating to errors by health workers or several incidents of irregularities as emergencies